Pericárdio bovino utilizado como remendo no sistema cardiovascular - Pires, Adilson Casemiro [UNIFESP] (1997)
The bovine pericardium, preserved into glutaraldehyde, in making valvar phostheses, is well known. Although largely used in the form of scrap, this was little studied. With this intention, 21 dogs were submitted to surgical patch of a standardized bovine pericardium scrap partially substituting, the aorta left atrium and pericardial walls. The dogs were randomly separated in three groups according to the reoperation time. Group 1 with 6 reoperated dogs between 33 and 43 days; group 2 with 7 reoperated dogs between 120 and 165 days and group 3 with 8 reoperated dogs between 225 and 305 days. The micro and macroscopic examinations showed: (1) the wrinkled surface of the scrap adhered to the neighboring structures, while the smooth surface implanted on pericardium adhered a little to epicardium; (2) the bovine pericardium scrap did not suffered structural change, independently of the implant location; (3) the final area of the left atrial patch was significantly smaller than the aortic and pericardial patches, to the dogs of groups 2 and 3; (4) the atrial patch area diminished significantly, while the aortic and pericardial have not been changed with time; (5) the pericardial scrap thickness was significantly smaller than the left atrium and aortic ones, in the dogs of group 3; (6) the formation of a fibrous connective tissue layer occurred on the smooth surface of the scraps implanted on the left atrium and aorta. The internal apposition tissue thickness was significantly greater on left atrium than on the aorta, in groups 1 and 2; (7) the internal apposition tissue of the atrial and aortic patches underwent calcification in dogs of groups 2 and 3; (8) the internal apposition tissue of atrial and aortic patches showed neoformation of elastic fibers that increased sharply as the implant time passed by. With this finding, we can conclude that the behavior of the bovine pericardium preserved into glutaraldehyde, as a scrap, for making a patch, in vascular surgery, depends on: (1) the contact surface; (2) the tension to which it is submitted; (3) the contact with the circulation.